Debates Over The " Xutba " in the Early XX Century - Sharifjon Islamov (Zien Journals, 2022)
At the beginning of the twentieth century, local reformers proposed an initiative to innovate and change the religious sphere. It, however, consisted of translating the lectures in Arabic, which had been conducted in the traditional form until then, into the local Turkic language. The change in the industry behind these proposals of local reformers has been preserved to this day. The article discusses the idea of reform and how one understands and interprets the term "sermon" in the process of this radical change, and the content of the debates on the example of periodicals.
Keywords: Correction; sermon; fard; Friday